Dental caries prevalence in children up to 36 months of age attending daycare centers in municipalities with different water fluoride content - Tiano, Ana Valéria Pagliari [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Orlando [UNESP]; Saliba, Nemre Adas [UNESP] (FapUNIFESP (SciELO), 2009)
This study determined the prevalence of cavitated caries lesions (CCL) and early childhood caries (ECC), and the contribution of some variables in children up to 36 months of age attending daycare centers in municipalities with different fluoride levels in the water supply: AFC (adequate fluoride content) and LFC (low fluoride content). After approval of the Ethics Committee, the parents were interviewed. The children were clinically examined using the same codes and criteria established by the WHO (World Health Organization) and the ADA (American Dental Association). Fisher's exact test (p<0.05) was applied for statistical analysis of data. The dmft indices calculated in the LFC and AFC municipalities were 0.57 and 0.68, respectively. Considering all children examined, 17.6% presented CCL and 33.8% ECC. The economic classification, mother's education level and duration of breastfeeding were considered statistically significant with regards to CCL prevalence. The age group, duration of the habit of drinking milk before bedtime and age at which oral hygiene started were considered statistically significant with regards to ECC prevalence.
Keywords: Dental caries; Early childhood caries; Oral health